Contextual-based student worksheets designed to facilitate mathematics representation ability - Fitriya, Haya Okta; Permatasari, Dian (Jurnal Kajian Pembelajaran Matematika, 2022)
Representation is one of the objectives of learning mathematics, but the representation ability is still low. Thus, the purpose of this study was to develop a contextual-based Student Worksheet on similarity and congruence material to facilitate students' mathematical representation skills. This research was Research and Development. The research used the PPE development model developed by Richey and Klein with three stages of development: planning, production, and evaluation. The results showed that the contextual-based student worksheet on similarity and congruence material to facilitate students' mathematical representation skills was declared valid based on the expert validator's assessment with an average validity value of 0.81 and included in the high criteria.